Cervical Chondrocutaneous Branchial Remnants: A Rare Congenital Anomaly of the Neck. A Case Series, Literature Review, and Associated Anomalies - Şimşekcan, Efe; Sarıay, Büşra; Turcan, Didem (Facial Plastic Surgery, 2023)
Cervical chondrocutaneous branchial remnants (CCBRs) are rare anomalies found in the neck. These remnants can be easily misdiagnosed due to their low incidence, and they are often associated with other anomalies. Previous studies have reported an association with other anomalies in up to 76% of cases. In this article, the authors present a case series of two patients with bilateral CCBRs and investigate the associated anomalies through a literature review. Patients diagnosed with CCBRs who presented with cervical masses were included. Records were reviewed to investigate factors such as sex, location of the CCBRs, associated anomalies, timing of operations, and cartilage pathology. A surgical excision technique was employed, and the study also included a literature review focusing on reports related to CCBRs and associated anomalies. Two patients, a 3-year-old boy and a 17-year-old adolescent girl, with bilateral CCBRs underwent surgical excision. Patient demographics, prevalence, and characteristics of associated anomalies in CCBR cases were documented in the literature review. This case series presented two successful surgical excisions of CCBRs without complications or recurrence at 1 year of follow-up. The study emphasized the importance of thorough evaluation and assessment for associated anomalies in various body systems due to the potential co-occurrence of CCBRs with other anomalies.
Keywords: abnormalities/multiple; branchial region/abnormalities; cartilage/abnormalities; choristoma/diagnosis; neck/abnormalities